Pojistná ochrana podnikatelského subjektu - Barák, Dominik (Vysoké učení technické v Brně. Fakulta podnikatelská, 2023)
Bakalářská práce je zaměřena na pojistnou ochranu vybrané společnosti. Nejprve je v práci shrnuta základní teorie, která je důležitá pro pochopení celé práce. Následně se autor zabývá analýzou rizik vybrané společnosti, jejíž výstupy jsou poté poptány u vybraných pojistitelů působících na tuzemském trhu. V poslední části práce jsou jednotlivé nabídky srovnány a navrhnuta nejlepší pojistná ochrana z pohledu autora.

The bachelor's thesis is focused on the insurance protection of the selected company. First, the thesis summarizes the basic theory, which is important for understanding the entire thesis. Subsequently, the author deals with the risk analysis of the selected company, the outputs of which are then requested from selected insurers operating on the domestic market. In the last part of the work, the individual offers are compared and the best insurance protection is proposed from the author's point of view.
The Insurance Protection of the Business Entity
Keywords: Riziko; analýza rizik; pojištění; pojistná ochrana; pojišťovna; Risk; risk analysis; insurance; insurance protection; insurance company